Evaluation of an Epoxy-Based Nanosilicacomposite Lining in H2SO4 Solution for Anticorrosion of Sewerage Concrete Structures. (4th May 2020) - Dinh, Chau Van
Abstract : This work presents the performance of a SiO2 -epoxy nanocomposite lining for the anticorrosion of the concrete structures in sewer networks. Nanocomposite lining on the concrete substrate surface of the 15 phr (part per hundred epoxy resin) amine-cured epoxy polymer containing 3.0 phr of nano-SiO2 was prepared by intercalating epoxy into the SiO2 via direct mixing process. The silica exfoliation was monitored by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The barrier feature of epoxy the base nanocomposite against water and sulfuric acid solution was evaluated. The results showed that the nanocomposite lining was of a great barrier against these corrosive environments due to the intercalation and exfoliation caused by the dispersion of the SiO2 nanoparticles into the epoxy matrix. The rate of the H2 SO4 into the nanocomposite lining was also investigated by measurement of the depth of the sulfur element penetrated layer using the coupled Scanning Electron Microscopy (SEM)/Energy dispersive X-ray spectrometer (EDS). Deterioration behavior of the adhesion strength of the nanocomposite lining was studied. The nanocomposite lining shows a significant improvement of bond strength in comparison to the neat epoxy lining. The durability of the nanocomposite lining adhesion when the lining systems exposed to water and the sulfuric acid solution is also improved significantly.